Effects of cryogenic temperature on some mechanical properties of beech (Fagus orientalis Lipsky) wood - Özkan, Osman Emre (Springer Science and Business Media LLC, 2021)
It is important to know the changes in the mechanical properties of wood during freezing for engineering calculations of the wood material to be used in cold environments. Although this is important, the mechanical properties of wood at temperatures below − 100 °C have rarely been studied. In this study, the effects of cryogenic temperature (− 196 °C) on the bending strength, modulus of elasticity in bending and compression strength parallel to the grain of oven-dried and air-dried beech wood was investigated. As a result of the experiment, the mechanical strength properties of the wood increased during freezing. The increase in bending strength and modulus of elasticity values were higher in air-dried wood than those in oven-dried wood. However, the increase in compression strength values was determined at the same rates as 61% for air-dried and oven-dried wood. This increase in mechanical strength properties of wood during freezing could be explained by freezing of water in the wood, hardening of wood cell walls, decreasing intermolecular distance, increasing intermolecular force and stabilization of crystalline structure.